Ichthyofauna of the Aguaytía River Basin, Ucayali, Perú - Quezada García, María Giuliana (2017)
An annotated species fish list recorded in the Aguaytía River basin is presented. Fishes were collected between 1942 and 2009 in different years and seasons. This is the first inventories in Aguaytía river Basin, and for the Cordillera Azúl National Park. Fishes were mainly collected using seines of 10x3 m and of 5x2 m and 6 mm mesh. For fixation and preservation of samples were used 10% formaldehyde solution and 70% ethanol, respectively. Samples are in the Ichthyological Collection (MUSM) of the Museum of Natural History of San Marcos University. We analized 9917 specimens and recorded a total of 211 species of 28 families and nine orders.